Parents' participation in taking care of hospitalized children: a - vasli, parvaneh; Salsali, mahvash; Tatarpoor, parvane (Advances in Nursing & Midwifery, 2013)
Abstract Background and objective Although “parents' participation in taking care of hospitalized children” is considered as an indispensible principle today, it is still among the concepts with no consensus about it. The main objective of this study is to define “parents' participation in taking care of hospitalized children” using hybrid model. Materials and methods In this research analysis of “parental participation in parents' participation in taking care of hospitalized children” was performed using a hybrid model in three steps: literature review (theoretical step), field work, and combination of literature review and field work. Findings Based on the step of literature review, the best definition for the concept of “parental participation in taking care of hospitalized children” was selected. In the field work step, dimensions of mentioned concept were extracted; and finally definition of this concept by mixing theoretical and field work step was proposed as: mutual relationship and gaining parents’ trust, giving required information and educations to the parents about care and treatment process, asking parents for doing needed home care jobs, involving the parents in care processes, and finally defining participation/decision making authorities (clarifying the parents role). Conclusion The findings of this study elucidated dimensions of parental participation in NICU where giving attention to them can lead to their putting to practice. Key Words : Parental participation, Hospital, Nursing, Hybrid model *Corresponding Author: Mahvash Salsali, Faculty of Nursing & Midwifery, Tehran University of Medical Sciences, Tehran, Iran E-mail : m_salsali@hotmail.com REFERENCES -Aein F Alhani F Mohammadi E et al (2009). Parental participation and mismanagement: A qualitative study of child care in Iran. Nursing Health Science. 11(3) 221-227. -Aein F Alhani F Mohammadi E et al (2011). Struggling to create new boundaries: A grounded theory study of collaboration between nurses and parents in the care process in Iran. Journal of Advanced Nursing. 67 (4) 841–853. -Balling K Mccubbin M (2001). Hospitalized children with chronic illness: Parental care giving needs and valuing parental expertise. Journal of Pediatric Nursing. 16 (2) 110-119. -Chapados C Pineault R Tourigny J et al. (2002). Perceptions of parents’ participation in the care of their child undergoing day surgery: Pilot-study. Issues in Comprehensive Pediatric Nursing. 25(1) 59–70. -Corlett J Twycross A (2006). Negotiation of parental roles within family – centered care: A review of the research. Journal of Clinical Nursing. 15 (10) 1308-1316. -Coyne I (1996). Parent participation: A concept analysis. Journal of Advance Nursing. 23 (4) 733–740. -Coyne I Cowley S (2007). Challenging the philosophy of partnership with parents: A grounded theory study. International Journal of Nursing Studies. 44(6) 893–904. -Diaz-Caneja A Gledhill J Weaver T et al (2005). A child’s admission to hospital: A qualitative study examining the experiences of parents. Intensive Care Medicine. 31(9) 1248–1254. -Doss S DePascal P Hadley K (2011). Patient nurse partnership. Nephrology Nursing Journal. 38(2) 115-125. -Elo S Kyngas H (2008). The qualitative content analysis process.The Journal of Advanced Nursing. 62(1) 107-115. -Espezel H Canam CJ (2003) Parent–Nurse Interactions: Care of Hospitalized Children. Journal of Advanced Nursing. 44(1) 34–41. -Gamell A Corniero P Palazon P et al (2011). Parental presence during invasive procedures in Spanish pediatric emergency department: Incidence, perspective, and related anxiety. European Journal of Emergency Medicine. 18 (4) 202-207. -Homer C Marino B Cleary P et al (1999). Quality of care at a children`s hospital. Archive Pediatrics and Adolescent Medicine. 153 (11) 1123-1129. -Hopia H Tomlinson P Paavilainen E et al (2005). Child in hospital: Family experiences and expectations of how nurses can promote family health. Journal of Clinical Nursing 14 (2) 212-222. -Huchfield K (1999). Family-centered care: A concept analysis. Journal of Advanced Nursing.29 (5) 1178-1187. -Hupcey J Penrod J (2005). Concept analysis: Examining the state of science. Research for Theory and Nursing Practice 19 (2) 197-208. -Jolley J Shields L (2009). The evolution of family-centered care. Journal of pediatric nursing. 24 (2) 164-170. -Korfmacher J Green B Staerkel F et al. (2008) Parent Involvement in Early Childhood Home Visiting. Child Youth Care Forum. 37 (4) 171-196. -Kristensson-Hallstrom I (1999). Strategies for feeling secure influence parents' participation in care. Journal of Clinical Nursing. 8(5) 586-592. -Kristensson-Hallstrom I (2000). Parental participation in pediatric surgical care. American Operating Room Nurse Journal. 71 (5) 1021–10241, 1026-1029. -McEwan M Wills E (2010). Theoretical Basis for nursing [3 rd edition]. Philadelphia, Lippincott Williams &Wilkins Co. -Meleis A (2011). Theoretical Nursing, Development and Progress [5 th edition]. Lippincott Williams & Wilkins co. -O`Haire S Blackford J (2005). Nurse’s moral agency in negotiation parental participation in care. International Journal of Nursing Practice. 11(6) 250-256. -Power N Frank L (2008). Parent participation in the care of hospitalized children: A systematic review. Journal of Advanced Nursing. 62 (6) 622-641. -Shields L Nixon J (2004). Hospital care of children in four countries. Journals of Advanced Nursing. 45(5) 475–486. -Tourigny J Chapados C Pineault R (2005). Determinants of parental behavior when children undergo day-care surgery. Journal of Advanced Nursing. 52(5)490–497. -Ygge B Arnetz J (2004). A study of parental involvement in pediatric hospital care: Implications for clinical practice. Journal of Pediatric Nursing. 19 (3) 217-223. -Ygge B (2007).Nurses' perceptions of parental involvement in hospital care. Pediatric Nursing. 19(5) 38-40